Review of Koutny, Stria, Farris, Michael (eds.) 2020: The role of languages in intercultural communication / Rolo de lingvoj en interkultura komunikado / Rola języków w komunikacji międzykulturowej. Poznań: Rys - Fortes, Fabio (Investigationes Linguisticae, 2022)
Intercultural exchange is undoubtedly a fact of our time. Over the last few decades, globalisation has enabled people from various parts of the world to interact for various purposes, from tourism to business, from education to international politics, from people working abroad to war refugees finding a new home. This trend was further accentuated after the 2020 pandemic, which made distance on-line communication popular and accessible on a very large scale. Despite the bright side of this phenomenon, language remains an issue (not to say a barrier) for intercultural communication.